Hydrogeochemistry Fundamentals and Advances, Mass Transfer and Mass Transport - Tikhomirov, Viatcheslav V (John Wiley & Sons, Incorporated, 2016)
Water is the Earth's most precious resource. Until recent years, water was often overlooked as being overly abundant or available, but much has changed all over the world. As climate change, human encroachment on environmental areas, and deforestation become greater dangers, the study of groundwater has become more important than ever and is growing as one of the most important areas of science for the future of life on Earth. This three-volume set is the most comprehensive and up-to-date treatment of hydrogeochemistry that is available. The first volume lays the foundation of the composition, chemistry, and testing of groundwater, while volume two covers practical applications such as mass transfer and transport. Volume three, which completes the set, is an advanced study of the environmental analysis of groundwater and its implications for the future. This second volume focuses more deeply on hydrogeochemical processes, such as mass transfer and mass transport, element migration, and many others that are important for a more thorough and advanced understanding of the subject. Whether as a textbook or a reference work, this volume is a must-have for any library on hydrogeochemistry.